1991
DOI: 10.1002/hep.1840140418
|View full text |Cite
|
Sign up to set email alerts
|

The effect of GABA on serum and hepatic polyamine concentrations after partial hepatectomy in rats

Abstract: Serum and hepatic polyamine concentrations in-inhibitory properties (5-7 1. Although the mechanism eluding putrescine, spermidine and spermine were whereby GABA inhibits cell growth has yet to be documented at Various time intervals after Partial determined, GABA has been reported to alter ornithine hePatectomY in rats treated with GABA (500 PdW decarboxylase (ODC) activity, the enzyme primarily body wt) Or isotonic saline. Aside from a transient responsible for polyamine synthesis (8, 9). Of interest, effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…16 We have previously documented that at serum concentrations similar to those described in animal models and humans with FHF, GABA significantly inhibits hepatic regenerative activity. 7,9 We have also documented that GABA' s inhibitory effects are likely mediated via activation of hepatocyte membrane GABA A receptors. 10 Recently, we reported that ciprofloxacin reverses these inhibitory effects in ethanoland carbon tetrachloride-induced models of hepatic injury.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…16 We have previously documented that at serum concentrations similar to those described in animal models and humans with FHF, GABA significantly inhibits hepatic regenerative activity. 7,9 We have also documented that GABA' s inhibitory effects are likely mediated via activation of hepatocyte membrane GABA A receptors. 10 Recently, we reported that ciprofloxacin reverses these inhibitory effects in ethanoland carbon tetrachloride-induced models of hepatic injury.…”
Section: Discussionmentioning
confidence: 94%
“…5,6 ␥-Aminobutyric acid (GABA) is a potent inhibitory amino acid neurotransmitter that inhibits the growth of normal and malignant cells. 7,8 We have previously reported that elevated serum concentrations of GABA similar to those documented in animals and humans with FHF inhibit hepatic regenerative activity in the rat. 9 Recently, we reported that ciprofloxacin, a fluroquinolone antibiotic with GABA A receptor antagonist properties, reverses the inhibitory effects of acute ethanol exposure on hepatic regeneration and the extent of fibrosis in a carbon tetrachloride model of cirrhosis in rats.…”
mentioning
confidence: 84%
“…The immediate effects of portal occlusion on plasma levels of glucagon do not appear to have been studied, but certainly, plasma glucagon levels are elevated significantly within 30 min of portacaval shunting (181, which would account for the delay in animals in group 3 of this study. Other substances that interfere with the activity of ODC, such as y-aminoisobutyric acid (19) do not appear to have been measured after portal occlusion.…”
Section: Discussionmentioning
confidence: 83%
“…Although the precise mechanism by which ciprofloxacin enhances hepatic regeneration has yet to be determined, this agent's potent GABA A receptor antagonist properties may be relevant [16]. GABA is known to inhibit liver regeneration and is highly elevated in patients and animals with FHF [5,17]. We have shown previously that ciprofloxacin enhances liver regeneration in an animal model of fulminant hepatitis, and increases survival rate as well [18].…”
Section: Discussionmentioning
confidence: 94%